Divulgação científica digital de três instituições públicas de ciência e pesquisa de Roraima - Toniazzo, Rafael (2021)
The present paper is an investigation on the process of communication to the external public, especially on scientific dissemination, in the sense of communication to a lay public, in social media, from three public research and teaching institutions in the State of Roraima: Federal University of Roraima - UFRR, State University of Roraima - UERR and Federal Institute of Roraima - IFRR, by following sample posts on social media during 2019 and January 2020. This is a case study with content analysis. Social media and the internet, now a days , are part of life, in a way that changed the form of communication, the form of relationship and the way of exercising citizenship, given this reality, scientific dissemination gains redoubled value, on the one hand, due to the need for scientific dissemination to also happen and be present in digital media, and on the other, to share knowledge, teach and learn, to integrate and participate in the community, presenting their people research and their knowledge, providing opportunities for the subjects of that community, to a mutual benefit. Faced with budgetary constraints, institutions can demonstrate their work and value by presenting the results of their research via scientific dissemination, however, there was extraordinarily little scientific dissemination content. The work suggests the use of scientific dissemination via content marketing, as a communication strategy of the institutions, content that will bring the Scientific Content Seal of the Institution.